Resistance to Experimental Visceral Leishmaniasis in Mice Infected With Leishmania infantum Requires Batf3 - Soto, Manuel; Ramírez, Laura; Solana, José Carlos; Cook, Emma C. L.; Hernández-García, Elena; Charro-Zanca, Sara; Redondo-Urzainqui, Ana; Reguera, Rosa M.; Balaña-Fouce, Rafael; Iborra, Salvador (Frontiers in Immunology, 2020)
Unveiling the protective immune response to visceral leishmaniasis is critical for a rational design of vaccines aimed at reducing the impact caused by this fatal, if left untreated, vector-borne disease. In this study we sought to determine the role of Batf3-dependent conventional type 1 dendritic cells (cDC1) in the evolution of infection with Leishmania infantum, the causative agent of human visceral leishmaniasis in the Mediterranean Basin and Latin America. For that, Batf3-deficient mice in C57BL/6 background were infected with an L. infantum strain expressing the luciferase gene. Bioluminescent imaging, as well as in vitro parasite titration, demonstrated that Batf3-deficient mice were unable to control hepatic parasitosis as opposed to wild-type C57BL/6 mice. The impaired microbicide capacities of L. infantum-infected macrophages from Batf3-deficient mice mainly correlated with a reduction of parasite-specific IFN-γ production. Our results reinforce the implication of Batf3 in the generation of type 1 immunity against infectious diseases.